2018
DOI: 10.1080/09638237.2018.1521919
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ mental health and well-being in developing countries: a cross-sectional survey from Pakistan

Abstract: Background: Despite global recognition of the significance of adolescents' mental health it remains a neglected area in research and health policy in Pakistan. Aims: To examine the rates of depression and anxiety and to assess the level of well-being among Pakistani adolescents. Methods: A cross-sectional sample of 1124 adolescents (age 11-18) was recruited from schools in Rawalpindi, Pakistan. Results: 17.2% and 21.4% participants were identified to be probable cases of depression and anxiety respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 58 publications
(54 reference statements)
1
25
1
Order By: Relevance
“…Importantly, while adolescents make up 38% of its total population, research on Pakistani adolescent development and mental health has only slowly emerged since the mid-1990s (Qidwai, Ishaque, Shah, & Rahim, 2010). Only limited research has simultaneously examined two independent samples of adolescents from high-income versus LMICs such as Pakistan (Khalid, Qadir, Chan, & Schwannauer, 2019). Notably, there is little research exploring protective and resilience factors in resource-restricted settings (Kieling & Rohde, 2012).…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…Importantly, while adolescents make up 38% of its total population, research on Pakistani adolescent development and mental health has only slowly emerged since the mid-1990s (Qidwai, Ishaque, Shah, & Rahim, 2010). Only limited research has simultaneously examined two independent samples of adolescents from high-income versus LMICs such as Pakistan (Khalid, Qadir, Chan, & Schwannauer, 2019). Notably, there is little research exploring protective and resilience factors in resource-restricted settings (Kieling & Rohde, 2012).…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…The prevalence of psychological distress among adolescents in Eastern Mediterranean countries was 27.7% (≥2 items of no close friends, loneliness, anxiety, suicidal ideation, and suicide attempt) in Afghanistan [11], 16.8% (≥14 scores on GHQ-28) in Egypt [12], 17.7% (≥3 items of worthless, anxious, angriness, confusion, and insomnia) in Iran [13], and 17.2% probable depression and 21.4% probable anxiety (≥10 scores and ≥ 12 scores on the Hospital Anxiety and Depression Scale, respectively) in Pakistan [14]. The proportion of moderate to severe psychological distress (measured with the Kessler K-10) was 23.0% in a community-based study among adolescents (N = 1000) in Tanzania [15] and 10.5% among school-going adolescents in India [16], and the prevalence of psychological distress measured with the GHQ was 35.1% among adolescents in Ontario, Canada [17], and 24.2% among urban out of school adolescents (N = 480) in Nigeria [18].…”
Section: Introductionmentioning
confidence: 99%
“…A majority of the female students were found to be at risk for developing burn-out while the same could be said about half of the males. What needs to be ascertained is whether this difference actually points to a greater vulnerability of females to stress 29,30 and/or to some specific work related factors affecting females. 31 In another study conducted on Pakistani medical and dental students from Lahore, Najma Naz et al have also reported that females are more prone to depression, stress and anxiety than males.…”
Section: Discussionmentioning
confidence: 99%